CGIAR Research Program on Roots, Tubers and Bananas - Plan of Work and Budget 2019 - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR Research Program on Roots, Tubers and Bananas, 2019)
The CGIAR Research Program on Roots, Tubers and Bananas (RTB) is a partnership collaboration led by the International Potato Center implemented jointly with Bioversity International, the International Center for Tropical Agriculture (CIAT), the International Institute of Tropical Agriculture (IITA), and the Centre de Coopération Internationale en Recherche Agronomique pour le Développement (CIRAD), that includes a growing number of research and development partners. RTB brings together research on its mandate crops: bananas and plantains, cassava, potato, sweetpotato, yams, and minor roots and tubers, to improve nutrition and food security and foster greater gender equity especially among some of the world’s poorest and most vulnerable populations.